2020
DOI: 10.3390/foods9091288
|View full text |Cite
|
Sign up to set email alerts
|

Headspace Gas Chromatography Coupled to Mass Spectrometry and Ion Mobility Spectrometry: Classification of Virgin Olive Oils as a Study Case

Abstract: Due to its multiple advantages, ion mobility spectrometry (IMS) is being considered as a complementary technique to mass spectrometry (MS). The goal of this work is to investigate and compare the capacity of IMS and MS in the classification of olive oil according to its quality. For this purpose, two analytical methods based on headspace gas chromatography (HS-GC) coupled with MS or with IMS have been optimized and characterized for the determination of volatile organic compounds from olive oil samples. Both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
2
13
1
Order By: Relevance
“…However, it should be also highlighted that although hexanal has been related to green apple and grass sensory descriptors, allowing the differentiation of EVOOs from the rest of the categories, this compound has also been related to a mustinesshumidity, fusty, winey-vinegary, or rancid defect, depending on its concentration. [50] Moreover, (E)-2-hexenal, related to green notes, [38] can be highlighted for its high areas in both varieties in the last ripening stages, in accordance with other authors. [12] In addition, our results were also consistent with the literature, showing that, especially in the Picual variety, irrigated samples exhibited higher areas of (E)-2-hexenal and hexanal than the rainfed ones.…”
Section: Chemosensory Evaluationsupporting
confidence: 88%
See 2 more Smart Citations
“…However, it should be also highlighted that although hexanal has been related to green apple and grass sensory descriptors, allowing the differentiation of EVOOs from the rest of the categories, this compound has also been related to a mustinesshumidity, fusty, winey-vinegary, or rancid defect, depending on its concentration. [50] Moreover, (E)-2-hexenal, related to green notes, [38] can be highlighted for its high areas in both varieties in the last ripening stages, in accordance with other authors. [12] In addition, our results were also consistent with the literature, showing that, especially in the Picual variety, irrigated samples exhibited higher areas of (E)-2-hexenal and hexanal than the rainfed ones.…”
Section: Chemosensory Evaluationsupporting
confidence: 88%
“…Another volatile compound that has been related to sensory defects is ethyl acetate (winey, vinegary). [50,52] Although this compound has proved to be relevant in the differentiation of EVOO and non-EVOOs, due to it showing more concentration in LOO samples through a GC-IMS analysis, [50] in the present study it showed low areas in general terms for all the samples, so it might not influence the sensory profile.…”
Section: Chemosensory Evaluationcontrasting
confidence: 51%
See 1 more Smart Citation
“…Therefore, GC-MS or GC-IMS could not be determined as the best analytical technique. However, either technique could be used as a complementary technique for the other one [ 29 ]. More comprehensive information of volatile compounds could be revealed and discrimination of food samples could be conducted by the combination of GC-MS and GC-IMS [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ion mobility spectrometry (IMS) has been successfully applied for a large variety of purposes, such as food fraud detection [ 36 , 37 , 38 , 39 ], fire debris analysis [ 40 , 41 ], and also to uncover drugs and explosives [ 42 , 43 , 44 ]. As regards environmental issues, IMS has mainly been used to detect bacterial contamination [ 45 , 46 , 47 ], to characterize biodegraded PDPs [ 48 ] and, in combination with extraction techniques, to identify polycyclic aromatic hydrocarbons in water [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%